Complete plastome sequence of Artocarpus heterophyllus Lam. (Moraceae): An ediable fruit cultivated throughout the tropics - Jia-Xuan Wang; Xiao-Feng Zhang; Jian-Hua Wang; Kun-Kun Zhao; Zhi-Xin Zhu; Hua-Feng Wang (Mitochondrial DNA. Part B. Resources, 2019)
Artocarpus heterophyllus is an evergreen tree with 10–20 m height. It is distributed in tropical low-altitude areas, and is a tropical fruit with great economic value. Here, we report and characterize the complete plastome of A. heterophyllus in an effort to provide genomic resources useful for promoting its systematics research. The plastome of A. heterophyllus is found to possess a total length 160,389 bp with the typical quadripartite structure of angiosperms, contains two Inverted Repeats (IRs) of 25,708 bp, a large single-copy (LSC) region of 89,077 bp, and a small single-copy (SSC) region of 19,896 bp. The plastome contains 112 genes, consisting of 78 unique protein-coding genes, 30 unique tRNA genes, and 4 unique rRNA genes. The overall A/T content in the plastome of A. heterophyllus is 63.90%. The phylogenetic analysis indicated that A. heterophyllus is close to Morus cathayana within Moraceae in this study. The complete plastome sequence of A. heterophyllus will provide a useful resource for the conservation genetics of this species as well as for the phylogenetic studies of Moraceae.